Colicin translocation through the E. coli cell envelope - Francis, M-LR (2018)
Gram-negative bacteria have evolved mechanisms to kill other microbial species to compete for space and resources. One mechanism exploited by Escherichia coli is the production of bacteriocins called colicins, which target closely-related sensitive E. coli strains. Colicins bind with high affinity to outer membrane proteins on the surface of E. coli, and following contact with proteins in the periplasm and inner membrane, translocate a cytotoxic domain to kill the cell. Killing displays first-order kinetics which has been suggested to mean a single molecule is sufficient to kill a cell, although this has yet to be demonstrated. The mechanism by which a folded colicin can cross two membranes to kill cells is still unknown, due to the lack of tools available. The aim of this research was to develop fluorescence-based microscopy tools to visualise colicin entry into E. coli and probe the mechanism of translocation in vivo. ColE9 was labelled with organic fluorophores within its cytotoxic domain and retained its catalytic activity in vitro, however its in vivo activity was reduced. Microscopy was optimised using a ColE9 active site mutant and the AlexaFluor-647 dye, to generate a fluorescent probe capable of translocating into but not killing cells. Translocation of ColE9*AF647 across the outer membrane (OM) was dependent on the PMF, in particular the electrical potential. Translocation of single-molecules of ColE9*AF647 to the cytoplasm was visualised for the first time in vivo; ~4-5 molecules were observed per cell, in 30 minutes at 37 °C. Two populations of ColE9*AF647 molecules were present; a mobile fraction with a diffusion coefficient similar to cytoplasmic GFP (~4-10 µm2/s) and an immobile fraction, the origins of which are unknown. Finally, the rate-limiting step for ColE9 translocation across the OM was shown to be passage through OmpF or OmpC, which could be modulated by the fluorophore used. The present work demonstrates that Tol-dependent colicins translocate across the OM in an energy-dependent manner and must be completely unfolded in order to translocate through OmpF or OmpC.